Development of IPAS Learning Modules Based on Differentiated Instruction - Musfita, Musfita; Rasmitadila, Rasmitadila; Puspitasari, Kristanti Ambar (Journal of Educational Sciences, 2025)
One of the challenges faced by elementary school students in learning science concepts is low achievement, partly due to limited teaching materials that match their diverse characteristics. This study aims to develop a valid, practical, and effective Science and Social Studies (IPAS) module based on differentiated learning. The research used a Research and Development (R&D) approach with the 4-D model (Define, Design, Develop, Disseminate). Data were collected through interviews, questionnaires, expert validation, and learning tests with fourth-grade students at SDN 9 Rantau Bayur, South Sumatra. The results indicate that the module developed meets high standards of validity, practicality, and effectiveness. Its implementation in the classroom significantly improved student learning outcomes, showing that differentiated learning can enhance students’ understanding and engagement. The module not only serves as teaching material but also as a tool for teachers to implement learning that accommodates students’ readiness, interests, and profiles. The findings suggest that differentiated learning-based modules are a promising strategy to improve the quality of IPAS instruction in elementary schools. Furthermore, this study can serve as a reference for the development of similar teaching materials in other subjects or different levels of education.